1947
DOI: 10.1139/cjr47b-053
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and Surface Losses in Disperse Systems in Still and Turbulent Air

Abstract: Smoke chamber studies have been made of the ageing of ammonium chloride smokes under various controlled degrees of turbulent air motion as well as in still air. The changes in mass concentration and particle number were followed for 5.5 hr. under each set of conditions, and some data on particle size distribution were obtained. The logarithm of the mass concentration was found to vary linearly with time under all conditions. None of the particle number data lent themselves to interpretation on the basis adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1951
1951
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…I t has been shown previously (3,4) that experimental data obtained a t relative humidities of 15% to 30% are adequately described by equations based on quite general grounds, i.e., For personal use only.…”
Section: Analysis Of T H E Datamentioning
confidence: 99%
See 3 more Smart Citations
“…I t has been shown previously (3,4) that experimental data obtained a t relative humidities of 15% to 30% are adequately described by equations based on quite general grounds, i.e., For personal use only.…”
Section: Analysis Of T H E Datamentioning
confidence: 99%
“…Estimates of the apparent particle size distribution of selected thermal precipitator samples were made with the aid of a Patterson-Cawood graticule in some experiments. The details of all sampling and assessment techniques have been described elsewhere (3,4).…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, measurements of aerosol coalescence on Earth are influenced by coupled effects of Brownian motion, turbulent shear and acceleration, and gravitational settling, making the experiment design difficult. Some attempts focused on measuring the coagulation rate of solid aerosol particles, in stirred tanks 32,33 or in a turbulent pipe flow. 34 In these studies, coagulation effects are observed by measuring the decay of the aerosol number density once the turbulent flow is initiated.…”
Section: About Experimentsmentioning
confidence: 99%